Signature Pedagogies in Collaborative Creative Learning in Advanced Music Training, Education and Professional Development: A Meta-Synthesis - Creech, Andrea; Zhukov, Katie; Barrett, Margaret S. (Frontiers in Education, 2022)
Recent debates concerned with Western music performance training have grappled with the question of what kind of education and training will best equip music students to navigate an increasingly dynamic and complex professional environment. Increasingly, attention has turned to the role of collaborative creativity and how collaborative, creative skills can be nurtured. Therefore, this paper interrogates the signature pedagogies of collaborative creative learning in advanced music training, education and professional development. Two research questions were addressed: 1) how can creative collaboration in advanced music training, education and professional development be understood through the lens of signature pedagogies; and 2) what are the core values that underpin signature pedagogies of collaborative creativity in advanced music training, education and professional development. A meta-synthesis of relevant qualitative research published since 2000 was carried out. Ten studies were retained. At the implicit level of signature pedagogies of collaborative creativity, three third-order constructs included a commitment to learning as participation in a community of collaborative practice, valuing collaboration in a creative artistic identity, and the capacity to embrace ambiguity. A further three third-order constructs – relational, experiential and creative exploration - comprised the deep level of pedagogical principles. At the surface level, signature pedagogical practices were structured as social and situated, while reflection in, on and for action was at the core of collaborative, creative pedagogical practices.